La Tabula Aurea - Cselényi, István Gábor (Verbum – Analecta Neolatina, 2010)
Scientists of our time have the advantages ofmodern technology such as computers. In a matter of minutes you can find an author, a work or any expression. In the past there were only lexicons and concordances available for this purpose. One of the early encyclopedic studies on St. Thomas Aquinas’s life-achievement is the Tabula Aurea (‘Golden Table’), which was written in Latin by Pietro Bergamo in 1473, 200 years after Thomas Aquinas’s death. The Tabula not only lists every expression in St. Thomas’s works, it also states how often, where, and in what context they appear. This way we get a wholesome overview of Aquinas’s philosophy and theology. In this study I strive to present the Tabula, both its author and the work itself. Furthermore, through focusing on a selected example, the modern issue of being (ens) and "to be" (esse), I aim to prove that Bergamo and even Aquinas, whose message is so humbly reviewed by the Tabula, were very modern, well ahead of their times. This example is also a significant segment of Romanistics, the career history of an infinitive (esse) and a participle (ens).